Septic arthritis post anterior cruciate ligament reconstruction due to Clostridioides difficile. (December 2020) - Eustace, M.B.; Jennison, A.V.; McCarthy, K.L.
Abstract: Clostridioides difficile is an obligate anaerobe ubiquitous in the environment and is of particular interest in the healthcare setting as a cause of healthcare associated infection usually presenting with colitis. Extracolonic manifestations of C. difficile infection are less common with only rare reports of septic arthritis primarily in the setting of relative or overt immunocompromise. This report details the case of a 31-year-old immunocompetent male presenting with clinical features of septic arthritis, three weeks post right knee anterior cruciate ligament (ACL) reconstruction using a native hamstring tendon graft. C. difficile was isolated from two different samples of the synovial tissue from a subsequent arthroscopic washout and synovectomy. The ACL graft was retained. The isolate underwent whole genome sequencing and was found to be tcdA and tcdB gene deficient. Susceptibility testing showed susceptibility to benzylpenicillin and metronidazole. The patient received a two-week course of intravenous benzylpenicillin and four weeks of oral metronidazole. At one-year post cessation of antibiotics the patient has no clinical evidence of recurrence. This is the first known reported case of C. difficile septic arthritis in an immunocompetent patient. It demonstrates successful treatment of post-ACL septic arthritis with a graft retention strategy. Highlights: C. difficile is an uncommon cause of septic arthritis. C. difficile septic arthritis can occur in the absence of overt immunocompromise. Septic arthritis post ACL reconstruction can be successfully treated with a graft retention strategy.